2021
DOI: 10.3390/ijerph18189761
|View full text |Cite
|
Sign up to set email alerts
|

The Road from Pathological Narcissism to Suicidality in Adolescence: An Empirical Study

Abstract: Background: Clinical and empirical research evidenced a complex link between pathological narcissism and the suicidal process in adulthood. Given the relevance of suicidality and the peculiar narcissistic vicissitudes of adolescence, the proposed research investigated the relationship between pathological narcissism analyzed from the multi-dimensional perspective of the Diagnostic Interview for Narcissism (DIN) and suicidal ideation conducted in a sample of Italian Adolescents. Methods: One hundred and three I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…It is possible that the age of the individuals involved (>18) influenced the results. Indeed, previous research that has identified a significant difference in pre-/post-pandemic self-harm attitude levels is predominantly conducted in samples of young adolescents or adults (Boldrini et al, 2021; Moselli et al, 2021a ; Lai et al, 2021 ; Schwartz-Mette et al, Williams et al, 2021 ; Iob et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the age of the individuals involved (>18) influenced the results. Indeed, previous research that has identified a significant difference in pre-/post-pandemic self-harm attitude levels is predominantly conducted in samples of young adolescents or adults (Boldrini et al, 2021; Moselli et al, 2021a ; Lai et al, 2021 ; Schwartz-Mette et al, Williams et al, 2021 ; Iob et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Often, depressed adolescents fear the loss of approval and acceptance from significant others, engaging them in angry tirades. These internal fights against depressive affects and attempts to avoid feeling helpless by becoming angry instead can be viewed as efforts to again conquer a sense of superiority [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…In adolescent patients with this personality subtype, depressive symptoms might reflect their inner experience characterized by a strong sense of failure and a deep vulnerability to shame and humiliation (Cheek et al ., 2018 ). These young people constantly strive for perfection and accomplishments and are plagued by oscillations between feelings of superiority and triumph over the other and a sense of worthlessness and inferiority, suicidal ideation, and even conducts which characterize the “introjective” depression of Blatt ( 2004 ) (Lingiardi & McWilliams, 2017 ; Williams et al ., 2021 ). Lastly, adolescents with an emerging borderline personality syndrome are mainly characterized by a pervasive sense of identity diffusion, primitive defense mechanisms, affective instability and impulsivity, often leading them to act self-harming behaviors or suicide attempts, as well as chaotic interpersonal relationships, which originate from the conflict between an intense desire for dependence and an equally deep fear of abandonment (Kernberg, 1967 ).…”
Section: Discussionmentioning
confidence: 99%
“…, insecurity, hypersensitivity to criticism) connected to low self-esteem (Ogrodniczuk & Kealy, 2013 ; Tanzilli et al ., 2021 ), as well as of the need for relatedness and dependence on others (Rost et al ., 2018 ). In the treatment, they feel exposed to the clinician’s scrutiny, which can make them feel small, dependent, and humiliated (Kernberg et al ., 2000 ), and may tend to use suicidal ideation and behaviors to exert their power over the therapeutic relationship (Tanzilli et al ., 2021 ; Williams et al ., 2021 ). Overall, depressed patients with marked narcissistic characteristics have more trouble fully engaging in the therapeutic process; therefore, they tend to have more difficulties in benefiting from therapeutic interventions (Gabbard, 2009 ), frequently cause impasses or alliance breakdowns (Ronningstam, 2019 ), and, more generally, show high levels of abandonment (Lamkin, 2018 ).…”
Section: Discussionmentioning
confidence: 99%